2021
DOI: 10.3390/molecules26061705
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Molecular Docking Studies and In Silico ADMET Screening of New Heterocycles Linked Thiazole Conjugates as Potent Anti-Hepatic Cancer Agents

Abstract: Thiazoles are important scaffolds in organic chemistry. Biosynthesis of thiazoles is considered to be an excellent target for the design of novel classes of therapeutic agents. In this study, a new series of 2-ethylidenehydrazono-5-arylazothiazoles 5a–d and 2-ethylidenehydrazono-5-arylazo- thiazolones 8a–d were synthesized via the cyclocondensation reaction of the appropriate hydrazonyl halides 4a–d and 7a–d with ethylidene thiosemicarbazide 3, respectively. Furthermore, the thiosemicarbazide derivative 3 was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 36 publications
(27 reference statements)
0
21
0
Order By: Relevance
“…These results accord with the results of El Nahrawy et al [ 19 ]. In other words, to develop several pharmaceutical coatings expressing anti-HIV, antitumor, and antimicrobial actions, the 1,2,3-triazole dependent heterocycles are well manipulated [ 13 , 20 , 21 , 22 , 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…These results accord with the results of El Nahrawy et al [ 19 ]. In other words, to develop several pharmaceutical coatings expressing anti-HIV, antitumor, and antimicrobial actions, the 1,2,3-triazole dependent heterocycles are well manipulated [ 13 , 20 , 21 , 22 , 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, 3 exhibited three singlet signals at 8.36 and 9.65 ppm for CH-, OH and NH, respectively. Its 13 C-NMR spectrum The 1,3,4-thiadiazoles were also involved in diverse biological applications [12][13][14][15][16] mostly by virtue of the -N double bond and C-S-group. Thiadiazole moieties can act as two-electron donor systems and hydrogen-binding domains.…”
Section: Chemistrymentioning
confidence: 99%
“…Many antibacterial and antiviral drugs were documented to append the 1,3,4-thiadiazole scaffold in their structures (Figure 1). The 1,3,4-thiadiazoles were also involved in diverse biological applications [12][13][14][15][16] mostly by virtue of the -N double bond and C-S-group. Thiadiazole moieties can act as two-electron donor systems and hydrogen-binding domains.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20] Over the past few years, compounds containing thiazole and/or thiadiazole scaffold are attractive to medicinal chemistry due to their unique chemical properties and diversity of the biological activities. [20][21][22][23][24][25] Therefore, they have therapeutic effects against several diseases such as antimalarial, antimicrobial, antiproliferative agents and anti-inflammatory [26][27][28][29][30] besides their significant with various fungicidal activities . [31,32] In addition, many scientific reported have also demonstrated that the sulfonamide moiety itself possess interesting pharmacological activities and therapeutic functions.…”
Section: Introductionmentioning
confidence: 99%